A Moral Assessment of the Polish Israeli Declaration Following the 2018 Polish Anti-Defamation Law - Lewin, Eyal; Miller-Katav, Orit (Journal of Education Culture and Society, 2020)
Aim: This paper focuses on the question to what extent the Netanyahu-Morawiecki joint declaration of June 27, 2018 was indeed a moral one. Ignoring the realpolitik versus ideal politics discourse, our goal is to find out whether solely on an ethical level one can judge the moral qualities of the political concession. Concept: To conduct an ethical judgement process, we took the following steps: (I) A review of the Israeli narrative. (II) A review of the Polish narrative. (III) An account of some moral shortcomings in both the Israeli as well as the Polish narratives. Eventually, these steps enabled us to reach a certain moral conclusion regarding the Polish Israeli declaration. Cognitive Value: We conclude that the Polish Israeli joint declaration was indeed a moderate compromise that could enable positive forces on both sides to strengthen their national narratives – not necessarily on account of each other. Furthermore, it could also serve as a mechanism that can elevate Holocaust research as well as universal understandings of lessons that can be learnt from the darkest age of human history.